Surface Activity, Aggregation Behavior, and Wettability of a Mixture of Perfluorinated Branched Short Chain Sulfonate Surfactants and Hydrocarbon Cationic Surfactants in Dilute Solutions - Li, Jiaming (Langmuir : the ACS journal of surfaces and colloids, 2025)
Perfluorooctanesulfonic acid (PFOS) and perfluorohexyl sulfonic acid (PFHxS) cause environmental pollution problems and have gradually been phased out in the market. To this end, a sulfonic acid based fluorinated surfactant, BQSF-SS, was synthesized with the branched C6 perfluorochain as the hydrophobic chain and the benzene ring as the connecting group. The surface activity, interaction parameters, aggregation behavior, and wetting properties of the BQSF-SS/dodecyl trimethylammonium bromide (DTAB) complex system were systematically studied. The results indicate that BQSF-SS has good surface properties, with the critical micelle concentration (CMC) of 0.52 mmol/L and the critical surface tension (γCMC) of 23.19 mN/m. Through the calculation of the interaction parameter model, it has been confirmed that there is a strong interaction between BQSF-SS and DTAB: When the compounding ratio is 1:10, the γCMC of the mixed solution decreases to 20.25 mN/m, and the CMC decreases to 0.02 mmol/L. Moreover, the mixed solution has excellent wetting properties and can wet polytetrafluoroethylene (PTFE) plates with strong hydrophobic properties at extremely low concentrations (0.078 mmol/L). In addition, the increase in temperature is not conducive to the formation of surfactant molecular aggregates in a BQSF-SS solution. However, the effect of temperature on the BQSF-SS/DTAB composite solution is the opposite. As the temperature increases, the CMC of the composite solution decreases, which is also related to the interaction between the two surfactants